High Beam Controller For Vehicle Using Image Processing Techniques - Md. Khairul Amri Bin Nordin, Md. Khairul Amri (Universiti Teknologi Petronas, 2007)

(untitled)
Pattern recognition and image processing techniques has much influence in computer vision. Features have been developing to improve the system in order to solve problems in computer vision. There have been many attempts at applying this technology for human benefits. This project requires the author to improve existing High Beam Controller for Vehicles prepared by Syazwan Hamizin bin Mohd @ Sulaiman and his project partner, Nor Sulyanie bt Sulong in year 2005. The objective of this project is to modify the existing system to allow the detection of approaching vehicle more precise using image processing techniques. The existing system uses Light Dependent Resistors which have contra especially precision of detecting various light sources resulting errors to the system. At the end of this project, a working prototype should be produce which will be performed by the author and his partner. The author is assigned to do the software part which relevant software has been developed and will integrate with hardware part. The scope of study would be on the automotive lighting characteristics, imaging devices, image processing control software simulations, and integrated automotive lamp controller for vehicle lighting circuit. The methodology required for the program structure start with the image acquisition, image enhancement, edge detection, segmentation, feature extraction, recognition, and interpretation. The hardware part which prepared by the author’s partner gave a challenging task in order to integrate both software and hardware systems but offered an opportunity to experience how the technology is linked to the outside world.